DIGITAL TECHNOLOGIES FOR IMPLEMENTING CORPORATE SOCIAL RESPONSIBILITY - Zhukova G.S.; Dolbik-Vorobey T.A.; Ostrovskaya N.V.; Burlankov P.S.; Kremer N.Sh. (Scientific Journal of Pedagogy and Economics, 2020)
The world is undergoing significant changes in corporate social responsibility of business, caused by a number of factors and “challenges” of time, which raises the question of the fundamental transformation of CSR management principles and tools. The most significant in terms of influence on CSR and the opportunities that open up is the digitalization of public life: the development of the digital economy and its new tools (principles of a “distributed registry” or blockchain, online platforms, digital communications). At the same time, Russia has its own peculiarities, in particular, public-private partnership mechanisms are becoming one of the factors of changes and promising directions for the development of CSR. PPP models are becoming a tool for enterprises and large companies to realize their corporate responsibility in terms of maintaining, reconstructing and constructing social facilities (long-term social investments), while reducing costs for non-core activities by sharing them with the state. Modern society is highly committed to humanitarian principles, to promote which close cooperation between community and business is required. Such close relationship between society and business is translated into the concept of corporate social responsibility. Lately, the concept of social responsibility of business has become increasingly popular though it has not been clearly defined yet. The relevance of the topic is due to both increased attention to the issues of corporate social responsibility (CSR), and those requirements that are put forward in this area in connection with the spread of new technologies. The origin of interest in the topic is usually associated with the publication of H. Bowen’s monograph. In the future, it is developed in the writings of A. B. Carroll and A. K. Bachholtz, J. Moon, D. Vogel and others. The ambiguity of the concept of corporate social responsibility causes numerous disputes both regarding the interpretation of the term and the most important business tasks in this domain. In the article, the author considers how the modern institutional environment, which is emerging in the new economy, affects the implementation of these tasks. Methodologically, we use the approaches of institutional economic theory and evolutionary economics. The new economy, in which innovative changes lead to a fundamental modification of the behavior of economic entities, puts forward new requirements for the activities of individuals and firms. The number of workers in the information sphere is growing, the requirements for the level of education of workers are increasing, and the information opportunities of top management are increasing. Under such conditions, many CSR tasks can be implemented by the company more efficiently and in fundamentally new forms: the internal control system is improved, the degree of transparency of activities is increased, the Internet helps to develop common standards, and information tasks are successfully solved. The rapid introduction of new technologies into the economic life has a tremendous impact on the company’s activities in such a significant area as CSR. And although this influence is difficult to evaluate unambiguously and quantitatively, it is safe to say that it will be strengthened in the future.